Polymerase Chain Reaction (PCR) - Based Diagnosis of Huanglongbing (Citrus Greening) Disease in Salyan District of Nepal - Chhetri, S B; Shrestha, M.; Shrestha, S. (Journal of Agriculture and Environment, 2019)
Available with full text.